Evaluation of eutrophication in the Ria Formosa coastal lagoon, Portugal - Newton, Alice (2003)
The Ria Formosa is a shallow mesotidal lagoon on the south coast of Portugal, with natural biogeochemical cycles essentially regulated by tidal exchanges at the seawater boundaries and at the sediment interface. Existing data on nutrients in the water column and the sediment, together with chlorophyll a and oxygen saturation in the water column,compared using different models for assessing eutrophication. The European Environmental Agency criteria are based on the comparison of nutrient concentrations which indicate that the situation in the Ria Formosa is ‘‘poor’’ to ‘‘bad’’. In contrast, the United States Estuarine Eutrophication Assessment is based on symptoms, including high chlorophyll a and low oxygen saturation, which indicate that the Ria Formosa is near pristine. Despite these contradictions, a preliminary assessment by Driving forces, Pressures, State, Impact, Reponses(DPSIR) of eutrophication demonstrate the potential for episodic eutrophic conditions from treated and untreated domestic effluent as well as from non-point source agricultural run off. Sediments are also an important source of nutrients in the lagoon, but their contribution to potential eutrophic conditions is unknown.